Relation between symptoms and profiles of coronary artery blood flow velocities in patients with aortic valve stenosis: a study using transoesophageal Doppler echocardiography. Issue 4 (April 1996) - Omran, H.; Fehske, W.; Rabahieh, R.; Hagendorff, A.; Lüderitz, B.
Abstract : OBJECTIVE: To analyse profiles of coronary artery flow velocity at rest in patients with aortic stenosis and to determine whether changes of the coronary artery flow velocities are related to symptoms in patients with aortic stenosis. DESIGN: A prospective study investigating the significance of aortic valve area, pressure gradient across the aortic valve, systolic left ventricular wall stress index, ejection fraction, and left ventricular mass index in the coronary flow velocity profile of aortic stenosis; and comparing flow velocity profiles between symptomatic and asymptomatic patients with aortic stenosis using transoesophageal Doppler echocardiography to obtain coronary artery flow velocities of the left anterior descending coronary artery. SETTING: Tertiary referral cardiac centre. PATIENTS: Fifty eight patients with aortic stenosis and 15 controls with normal coronary arteries. RESULTS: Adequate recordings of the profile of coronary artery flow velocities were obtained in 46 patients (79%). Left ventricular wall stress was the only significant haemodynamic variable for determining peak systolic velocity (r = -0.83, F = 88.5, P < 0.001). The pressure gradient across the aortic valve was the only contributor for explaining peak diastolic velocity (r = 0.56, F = 20.9, P < 0.001). Controls and asymptomatic patients with aortic stenosis (n = 12) did not differ for peak systolic velocity [32.8 (SEM 9.7) v 27.0 (8.7) cm/s, NS] and peak diastolic velocity [58.3 (18.7) v 61.9 (13.5) cm/s, NS]. In contrast, patients with angina (n = 12) or syncope (n = 8) had lower peak systolic velocities and higher peak diastolic velocities than asymptomatic patients (P < 0.01). Peak systolic and diastolic velocities were -7.7 (22.5) cm/s and 81.7 (17.6) cm/s for patients with angina, and -19.5 (22.3) cm/s and 94.0 (20.9) cm/s for patients with syncope. Asymptomatic patients and patients with dyspnoea (n = 14) did not differ. CONCLUSIONS: Increased pressure gradient across the aortic valve and enhanced systolic wall stress result in characteristic changes of the profile of coronary flow velocities in patients with aortic stenosis. Decreased or reversed systolic flow velocities are compensated by enhanced diastolic flow velocities, particularly in patients with angina and syncope. This characteristic pattern of the profile of coronary artery flow velocities in patients with angina or syncope may be useful for differentiating those patients from asymptomatic patients.